Hubungan Model Pembelajaran Project Based Learning (PBL) Dengan Keterampilan Menulis Teks Deskripsi Pada Siswa Kelas IX G di SMP Negeri 1 Simpang Hulu Kabupaten Ketapang - mawarnia, iga; Wiranty, Wiendi; Safitri, Yuyun (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
Abstract: This study aims to determine the relationship between the implementation of the Project Based Learning (PBL) learning model and the descriptive text writing skills of class IX G students of SMP Negeri 1 Simpang Hulu, Ketapang Regency. The background of this study is based on the low writing skills of students, especially in writing descriptive texts that require creative thinking skills, language mastery, and structural accuracy. The Project Based Learning model was chosen because it is considered capable of increasing active student involvement, fostering a sense of responsibility, and developing critical and creative thinking skills through project-based learning activities. The method used is correlational research with a quantitative approach. The study population included all class IX students of SMP Negeri 1 Simpang Hulu, and the sample was determined by simple random sampling, namely class IX G, which consisted of 31 students. Data were collected through a questionnaire to measure the level of PBL implementation and a writing test to assess descriptive text writing skills. Data analysis was carried out using normality and linearity tests using statistical software. The results showed that the implementation of the PBL learning model was in the high category with an average value of 3.66 on a scale of 1–4. Students' descriptive text writing skills were also classified as good to very good, with scores ranging from 75 to 90. The linearity test showed a significance value of p = 0.000 (<0.05), indicating a significant linear relationship between the implementation of PBL and descriptive text writing skills. The Deviation from Linearity value of 0.372 (>0.05) indicates that the relationship is consistent and does not deviate from the linear pattern. Therefore, it can be concluded that the better the implementation of the Project-Based Learning model, the higher the students' descriptive text writing skills. This model is effective in creating an active, collaborative, and meaningful learning environment, while simultaneously enhancing students' critical thinking skills and creativity in Indonesian language learning. Keywords: Project-Based Learning, Writing, Descriptive Text, Indonesian Language Learning